2023
DOI: 10.3122/jabfm.2022.220143r1
|View full text |Cite
|
Sign up to set email alerts
|

Expert Consensus Statement on Proficiency Standards for Dermoscopy Education in Primary Care

Abstract: Background: Primary care providers (PCPs) frequently address dermatologic concerns and perform skin examinations during clinical encounters. For PCPs who evaluate concerning skin lesions, dermoscopy (a noninvasive skin visualization technique) has been shown to increase the sensitivity for skin cancer diagnosis compared with unassisted clinical examinations. Because no formal consensus existed on the fundamental knowledge and skills that PCPs should have with respect to dermoscopy for skin cancer detection, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Recently, Tran et al proposed an expert‐approved list of key dermoscopic features of skin tumours to be taught in training programs for PCPs 57 . We found that all of the core dermoscopic features proposed in their fundamental list of basic skills required to selectively triage benign and malignant skin lesions are taught in the ST.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, Tran et al proposed an expert‐approved list of key dermoscopic features of skin tumours to be taught in training programs for PCPs 57 . We found that all of the core dermoscopic features proposed in their fundamental list of basic skills required to selectively triage benign and malignant skin lesions are taught in the ST.…”
Section: Discussionmentioning
confidence: 76%
“…-28% margin of non-inferiority programs for PCPs. 57 We found that all of the core dermoscopic features proposed in their fundamental list of basic skills required to selectively triage benign and malignant skin lesions are taught in the ST. In the same line of thought, we deliberately excluded from the ST skin tumours that do not present specific dermoscopic features or that are difficult to diagnose using dermoscopy, such as adnexal tumours.…”
Section: F I G U R Ementioning
confidence: 89%